Characterization of nodal/TGF-lefty signaling pathway gene variants for possible roles in congenital heart diseases. - Xia Deng; Jing Zhou; Fei-Feng Li; Peng Yan; Er-Ying Zhao; Ling Hao; Kai-Jiang Yu; Shu-Lin Liu (PLoS ONE, 2014)
BACKGROUND: Nodal/TGF-Lefty signaling pathway has important effects at early stages of differentiation of human embryonic stem cells in directing them to differentiate into different embryonic lineages. LEFTY, one of transforming growth factors in the Nodal/TGF-Lefty signaling pathway, plays an important role in the development of heart. The aim of this work was to find evidence on whether Lefty variations are associated with congenital heart diseases (CHD). METHODS: We sequenced the Lefty gene for 230 Chinese Han CHD patients and evaluated SNPs rs2295418, rs360057 and g.G169A, which are located within the translated regions of the genes. The statistical analyses were conducted using Chi-Square Tests as implemented in SPSS (version 13.0). The Hardy-Weinberg equilibrium test of the population was carried out using online software OEGE, and multiple-sequence alignments of LEFTY proteins were carried out using the Vector NTI software. RESULTS: Two heterozygous variants in Lefty1 gene, g.G169A and g.A1035C, and one heterozygous variant in Lefty2 gene, g.C925A, were identified. Statistical analyses showed that the rs2295418 (g.C925A) variant in Lefty2 gene was obviously associated with the risk of CHD (P value = 0.016<0.05). The genotype frequency of rs360057 (g.A1035C) variant in Lefty1 gene was associated with the risk of CHD (P value = 0.007<0.05), but the allele frequency was not (P value = 0.317>0.05). CONCLUSIONS: The SNP rs2295418 in the Lefty2 gene is associated with CHD in Chinese Han populations.